Composition Dependent Electrical Transport in Si1−xGex Nanosheets with Monolithic Single‐Elementary Al Contacts. Issue 44 (22nd September 2022) - Wind, Lukas; Sistani, Masiar; Böckle, Raphael; Smoliner, Jürgen; Vukŭsić, Lada; Aberl, Johannes; Brehm, Moritz; Schweizer, Peter; Maeder, Xavier; Michler, Johann; Fournel, Frank; Hartmann, Jean‐Michel; et al.
Abstract: Si1− x Ge x is a key material in modern complementary metal‐oxide‐semiconductor and bipolar devices. However, despite considerable efforts in metal‐silicide and ‐germanide compound material systems, reliability concerns have so far hindered the implementation of metal‐Si1− x Ge x junctions that are vital for diverse emerging "More than Moore" and quantum computing paradigms. In this respect, the systematic structural and electronic properties of Al‐Si1− x Ge x heterostructures, obtained from a thermally induced exchange between ultra‐thin Si1− x Ge x nanosheets and Al layers are reported. Remarkably, no intermetallic phases are found after the exchange process. Instead, abrupt, flat, and void‐free junctions of high structural quality can be obtained. Interestingly, ultra‐thin interfacial Si layers are formed between the metal and Si1− x Ge x segments, explaining the morphologic stability. Integrated into omega‐gated Schottky barrier transistors with the channel length being defined by the selective transformation of Si1− x Ge x into single‐elementary Al leads, a detailed analysis of the transport is conducted. In this respect, a report on a highly versatile platform with Si1− x Ge x composition‐dependent properties ranging from highly transparent contacts to distinct Schottky barriers is provided. Most notably, the presented abrupt, robust, and reliable metal‐Si1− x Ge x junctions can open up new device implementations for different types of emerging nanoelectronic, optoelectronic, and quantum devices. Abstract : The authors report monolithic and single‐crystal heterostructures with abrupt junctions, obtained from a thermal Al‐Si1− x Ge x exchange reaction. Integrated into Schottky barrier transistors with single‐elementary Al contacts, Si1− x Ge x composition‐dependent properties ranging from highly transparent contacts to distinct Schottky barriers are found. The obtained metal‐Si1− x Ge x heterostructures can be a key building block for emerging nanoelectronic, optoelectronic and quantum devices.